2021
DOI: 10.1002/pa.2722
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between financial inclusion and financial development in India: Is there any link?

Abstract: A dynamic chain of financial activities and services can be served from debtors to creditors in the international economy through an efficient and effective financial sector. The motivation behind this study is to investigate the linkages between financial inclusion and financial development in India during the period (1980–2017). For this, the study employ principal component analysis (PCA) to construct both financial inclusion index and financial development index which measures financial access and financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 55 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…According to Lenka (2021), the financial sector can be viewed in two ways: financial development and financial inclusion. Financial development aims to promote innovation and competition, making transactions in the financial sector more affordable (Hartmann et al, 2007).…”
Section: Understanding Financial Inclusionmentioning
confidence: 99%
“…According to Lenka (2021), the financial sector can be viewed in two ways: financial development and financial inclusion. Financial development aims to promote innovation and competition, making transactions in the financial sector more affordable (Hartmann et al, 2007).…”
Section: Understanding Financial Inclusionmentioning
confidence: 99%
“…From the Chinese stock market, Yang and He (2019) also concluded that financial innovation regulations had a positive impact on the financial market from 2008 to 2015. Lenka (2022) investigated the relationship between financial inclusion and financial development for the Indian economy from 1980 to 2017; results from the study showed a unidirectional causal relationship. This further promotes the view that financial inclusion plays an important role in the development of the financial sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of the analysis indicates that there is short-run causality running from commercial bank branches to human development index. Lenka (2021) investigates the linkages between financial inclusion and financial development in India from 1980 to 2017. The author used the principal component analysis methodology to construct both financial inclusion index and financial development index.…”
Section: Literature Reviewmentioning
confidence: 99%